PENGARUH LINGKUNGAN KERJA DAN BUDAYA ORGANISASI TERHADAP KINERJA KARYAWAN PT. BANK RIAU KEPRI CAPEM DURI - Amelia Pratiwi; Nuryanti '; Iwan Nauli Daulay (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2014)
This study was conducted to determine the effect of work environment and organizational culture and work simultaneosly on employee performance PT. Bank Riau Kepri Capem Duri Riau, and to determine and analyze the effect of work environment and organizational culture on employee performance partially.Variable in this study is thr work environment, organization culture and performance and while the population is all employees in PT. Bank Riau Kepri Capem Duri amounted to 35 people. The sampling method the author uses census, all the population be the sample. In this study the data obtained will be processed by multiple linear regression models. Regression methods can be used to show how the independent variables affect the dependent variable.The first hypothesis test result indicate that the work environment affect the performance of the employees at PT. Bank Riau Kepri Capem Duri. The second hypotesis testresults show thatr the influence of organizational culture on the performance of employees at PT. Bank Riau Kepri Capem Duri. F test results have a relationship with the dependent variable.that is variabler work environment and organizational culture and simultaneously and significant influence on employee performance at PT. Bank Riau Kepri Capem DuriKeywords : Work Environment, Organization Culture And Performance